Resting metabolic rate prediction equations in teenagers: history and validity - Paulo Henrique Santos da Fonseca; Maria de Fátima da Silva Duarte (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n4p405 The resting metabolic rate (RMR) has been utilized routinely by clinics to predict the energy necessary for patients. Additionally, governmental agencies and health organizations define the energy necessary for the population and the energy orientation for athletes who play sports. Many recognize the value of the RMR, but it is not always possible to measure it by using calorimetry, so it is suggested to use equations of prediction for this variable. However, RMR prediction equations must be used in such a way that allows its frequent reexamination to guarantee efficiency. This article has three purposes: 1) to analyze the development history of the traditional equations by Harris and Benedict (1919), Schofield (1985), WHO/FAO/UNU (1985), and Henry and Rees (1991) (these authors routinely used the traditional equations to measure the RMR in teenagers); 2) to analyze the studies that tested the validity of these equations in the population of teenagers; 3) to argue and point out possible intervening factors on the RMR results of teenagers, thus guiding to election of independent variables when developing equations for Brazilian's population. After analyzing the equations, it is possible to conclude that: 1) the equations had been developed by having a given base of compiled evaluations from the beginning of the Twentieth Century; 2) the studies that tested the validity of these equations demonstrated great variability in the results, confirming the impossibility to have a unique/universal equation. This study also showed that new RMR prediction equations must be developed for specific populations taking into consideration the race and where the individual resides.